Flood Inundation Mapping in the Cimanceuri River through Integration of HEC-HMS and HEC-RAS as A Basis for Flood Risk Management - Fikri, Rijal Muhammad; Herawati, Henny; Pranoto, Wati Asriningsih (Jurnal Teknik Sipil, 2025)
Flooding has become a recurring hazard in parts of Tangerang Regency, particularly in the Cimanceuri River Basin, where communities are increasingly vulnerable to inundation. Repeated flood events recorded over recent years highlight the urgent need for data-driven approaches in flood risk mitigation and management. This study aims to model the basin's hydrological characteristics and hydraulic regime using the eventual inundation map to support flood risk management planning in Tangerang Regency. To do so, HEC-HMS was used to compute flood discharge during the March 3, 2025, event in Pagedangan Subdistrict. The computed discharge was used as input to generate the inundation map using HEC-RAS 2D, supported by LiDAR-derived digital elevation model data. This area imagery of flood inundation served as the basis for model calibration. The results showed that the developed model accurately mapped the inundation, yielding a simulated total inundation area of 6.705 hectares.